Being and Meaning : Reality and Language in Bhartrhari and Heidegger - Kadankavil , Thomas (Journal of Dharma, 2002)
The phenomenon of the encounter of religions and philosophies of the West and the East has become a very conspicuous one with the increasing number of comparative studies in the recent times. Dr. Sebastian Alackapally’s Being and Meaning is another welcome addition to this literature to make the West and the East meet. One of the ever-alive dreams of this endeavour is that their philosophical and religious formulations, since they converge so closely, are bound to meet at one point. It has become an open question as we consider the roots and aspirations behind these formulations of the philosophical and religious ,quests. The truth, however, is that ultimately, when these formulations are viewed as pure germinal intuitions, all philosophical and religious reflections, both in the West and the East, are inspired by the same vision of man’s true and original nature. This seems to be the working’hypothesis in the book under review.